Komparasi Studi: Desain Struktur Organisasi Perguruan Tinggi Swasta menuju Organisasi Kompetitif - Purwanto, Purwanto; Sari, Endah Murtiana; Rismawati, Rismawati (Universitas Sains dan Teknologi Komputer, 2025)
Organizational structure is crucial because it determines the tasks and functions, as well as how coordination and communication are carried out within the organization. Higher education management requires appropriate organizational structure design, especially in private universities, where there are differences between operations and asset management. The organizational structure must align with the organization's development maturity level to be adaptive, mature, and capable of adapting to emerging developments. This study aims to design an organizational structure for private universities that have unique characteristics and require professional management. Through a comparative analysis of various literature studies and case studies from three different private universities, this study aims to provide recommendations for an appropriate organizational structure to manage private universities in Indonesia. The results of this study can help develop organizational structures for private universities in Indonesia to improve communication and coordination and become professional organizations in the long term.